Hadis-Hadis tentang Peserta Didik - dan Nur Hidayah, Amiruddin Siahaan (Nadwa, 2014)
This article explains that learners should earnestly seekÂ  knowledge or perseverance in either theology or science. In addition, if the students have gained knowledge, then that knowledge should be employed well and teaches it to others. Meanwhile, science is only acquired by learning. Learner is one component input in the education system, which is further processed in the educational process, so that it becomes a qualified human in accordance with the national education goals. A student has a very important role in education. Itwas described in many traditions (hadis \ ) associated with virtue, character, and requirements of the learners. These hadis \ will be explained later in this article and will be takhri > j to determine the position of these traditions. AbstrakArtikel ini menjelaskan bahwa peserta didik hendaknya bersungguh-sungguh atau tekun dalam mencari ilmu baik ilmu agama maupun ilmu pengetahuan. Selain itu peserta didik apabila telah mendapatkan ilmu, maka hendaknya ilmutersebut dipergunakannya dengan baik dan diajarkannya kepada orang lain. Ilmu hanya diperoleh dengan belajar. Peserta didik adalah salah satu komponen masukan dalam sistem pendidikan, yang selanjutnya diproses dalamproses pendidikan, sehingga menjadi manusia yang berkualitas sesuai dengan tujuan pendidikan nasional. Seorang pelajar memiliki peran yang sangat penting dalam pendidikan. Hal itu dijelaskan dalam banyak hadis yang berkaitan dengan kebajikan, karakter, dan persyaratan peserta didik. Hadis-hadis ini akan dijelaskan nanti dalam artikel ini dan akan di takhri>j untuk mengetahui posisi hadis-hadis tersebut.